As negociações coletivas do setor bancário paulista: 1979/1985 - Amorim, Wilson Aparecido Costa de (1992)
This study is about the collective bargaining at the banking sector of São Paulo state during the period 1979/1985. The concept of the collective bargaining is understood as a part of the labor relationship, where social, economic, politica1 and technological factors interact, as described in DUNLOP's' definition. In this system, under a particular context, the so called actors take part (workers, employees, government, and their respective organizations. By this sense we tried describe the collective bargaining context, the process of bargaining between the actors and their respective movements, and to define how these collective bargaining were structured. Before studding the bargaining at the banking sector we researched the collective bargaining during the period 1979/1985. We identified at this period important transformations like the growth of the union's power, as well as of direct bargaining between capital and labor, but weak evolution on the labor agreements. We studied the banking sector evolution after 1964 then described its employees union organization behavior. Studding the worker union organization from São Paulo, we identified worker's union at the capital and the Federation of state as the bargainers against the employees. After this, we analyzed how the co11ective bargaining with. the banks happened. At these bargaining we found a movement,bf centralization in their structures, and identified that the wage question was the main, almost the on1y one bargaining object, and finally we found bargaining that were concluded without labor's court decisions. At the end, we compared the banking sector collective bargaining and the overview of the other sectors emphasizing their results, process and structure